Spent : a comic novel - Bechdel, Alison, 1960- (Mariner Books, 2025)
"In Alison Bechdel's hilariously skewering and gloriously cast new comic novel confection, a cartoonist named Alison Bechdel, running a pygmy goat sanctuary in Vermont, is existentially irked by a climate-challenged world and a citizenry on the brink of civil war. She wonders: Can she pull humanity out of its death spiral by writing a scathingly self-critical memoir about her own greed and privilege? Meanwhile, Alison's first graphic memoir about growing up with her father, a taxidermist who specialized in replicas of Victorian animal displays, has been adapted into a highly successful TV series. It's a phenomenon that makes Alison, formerly on the cultural margins, the envy of her friend group (recognizable as characters, now middle-aged and living communally in Vermont, from Bechdel's beloved comic strip Dykes to Watch Out For). As the TV show Death and Taxidermy racks up Emmy after Emmy--and when Alison's Pauline Bunyanesque partner Holly posts an instructional wood-chopping video that goes viral--Alison's own envy spirals. Why couldn't she be the writer for a critically lauded and wildly popular reality TV show...like Queer Eye...showing people how to free themselves from consumer capitalism and live a more ethical life?!! Spent's rollicking and masterful denouement--making the case for seizing what's true about life in the world at this moment, before it's too late--once again proves that "nobody does it better" (New York Times Book Review) than the real Alison Bechdel"--